Symmetric and asymmetric committees - Ruth Ben-Yashar; Leif Danziger (Institute for the Study of Labor (IZA), 2011)
This paper studies the assignment of decision makers to two committees that make decisions by a simple majority rule. There is an even number of decision makers at each of various skill levels and each committee has an odd number of members. Surprisingly, even with the symmetric assumptions in the spirit of Condorcet, a symmetric composition of committees is not always optimal. In other words, decision makers with different skill levels should not generally be evenly divided among the committees. However, in the special case of only two skill levels, it is optimal to compose the committees evenly.
urn:nbn:de:101:1-20110621425
Keywords: D70; D71; D72; 330; committees; collective decision making; simple majority rule